2020
DOI: 10.1111/jsr.13142
|View full text |Cite
|
Sign up to set email alerts
|

Sleep of preschoolers during the coronavirus disease 2019 (COVID‐19) outbreak

Abstract: Coronavirus disease 2019 (COVID‐19) has resulted in a significantly large number of psychological consequences, including sleep health. The present study evaluated sleep patterns, sleep disturbances, and associated factors in Chinese preschoolers confined at home during the COVID‐19 outbreak. Caregivers of 1619 preschoolers (aged 4–6 years) recruited from 11 preschools in Zunyi, Guizhou province completed the Children’s Sleep Habit Questionnaire (CSHQ) between 17th and 19th February 2020. Data were compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
203
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(237 citation statements)
references
References 15 publications
26
203
4
4
Order By: Relevance
“…Our results on preschoolers are in agreement with this study and with another research carried out on Italian preschoolers in which the lockdown determined a delay of about 1 hour on bedtime and risetime[ 13 ]. This phase shift during lockdown in preschoolers is associated with a decrease in napping in our two younger groups, in agreement with a Chinese report in preschoolers[ 5 ]. In our study, school age children and adolescents showed the most relevant phase delay with about 28% of schoolers and 64% of adolescents falling asleep after 11 p.m. during lockdown vs. 0.87% and 12%, respectively, before.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results on preschoolers are in agreement with this study and with another research carried out on Italian preschoolers in which the lockdown determined a delay of about 1 hour on bedtime and risetime[ 13 ]. This phase shift during lockdown in preschoolers is associated with a decrease in napping in our two younger groups, in agreement with a Chinese report in preschoolers[ 5 ]. In our study, school age children and adolescents showed the most relevant phase delay with about 28% of schoolers and 64% of adolescents falling asleep after 11 p.m. during lockdown vs. 0.87% and 12%, respectively, before.…”
Section: Discussionsupporting
confidence: 93%
“…According to our study, different reports also showed that the most important negative consequence of the lockdown was the delay of sleep onset and offset. A recent study showed that the confined children had significantly later bedtime and waketime and increased nocturnal sleep duration[ 5 ]. Our results on preschoolers are in agreement with this study and with another research carried out on Italian preschoolers in which the lockdown determined a delay of about 1 hour on bedtime and risetime[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are aware of only one study that examined sleep patterns of children during the COVID‐19 crisis. In this recent study (Liu et al, 2020), sleep patterns and sleep disturbances of Chinese preschoolers were studied during the COVID‐19 home confinement. The findings showed that children demonstrated changes in sleep patterns characterised by later bedtimes and wake times, and longer nocturnal and shorter nap sleep durations, compared to children’s sleep patterns in non‐crisis time.…”
Section: Introductionmentioning
confidence: 99%